2023
DOI: 10.1371/journal.pone.0283709
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in primary healthcare utilization in Java Region—Indonesia

Abstract: Background Policymakers must understand primary healthcare utilization disparity to minimize the gap because they must seek fair service for every citizen. The study analyzes regional differences in primary healthcare utilization in Java Region-Indonesia. Methods The cross-sectional research analyzes secondary data from the 2018 Indonesian Basic Health Survey. The study setting represented Java Region-Indonesia, and the participants were adults 15 years or more. The survey explores 629,370 respondents. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They have coordination lines to their sub-level of community health services in the working area, such as sub-district PHC and posyandu (integrated service centres in rural areas). Their services address the population's healthcare needs and improve overall health outcomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…They have coordination lines to their sub-level of community health services in the working area, such as sub-district PHC and posyandu (integrated service centres in rural areas). Their services address the population's healthcare needs and improve overall health outcomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…And also impacted the hospital payment system in East Java and has the potential to increase fraud (Khoiri et al ., 2020). Moreover, a study on the implementation of the National Health Insurance at the Primary Health Center (PHC) found that this policy implementation was hampered by a lack of doctors, medical equipment (Eskawati et al ., 2018), poor access to health facilities (Putri et al ., 2021) and low (4.6%) utility of primary care other provinces on the island of Java (Wulandari et al ., 2023) These studies demonstrate the complexities of implementing a health system in East Java. Thus, this research aims to examine the frequency and specificity of health-related topics in local political campaigns during the gubernatorial elections, utilizing online news media as a source of information.…”
Section: Introductionmentioning
confidence: 99%